Indisciplina em sala de aula: posicionamento dos professores e avaliação de uma proposta de formação - Bocchi, Ketney Cristine Bonfogo (2007)
Having as point of reference the behavioural approach, which recommends the functional analysis of indiscipline in the classroom, the objectives of this research were detecting the standpoint from which a group of teachers considered indiscipline and applying an educational project so as to lead them to analyze indiscipline in the classroom functionally. The research was conducted in a state school located in the south zone of the city of São Paulo, Brazil, and involved the participation of 13 teachers of the third and fourth years of elementary school. Data was obtained by means of classroom observation, collective interviews and questionnaires. The educational project was implemented during the Collective Pedagogic Work Period, comprising 9 sessions, each of them lasting 30 minutes approximately. The data under analysis included the points of view of teachers concerning indiscipline in the classroom (their concept of indiscipline, the kind of behaviour that should be considered as indiscipline, the causes of indiscipline, the courses of action to be taken when confronted with such behaviour, and possible suggestions). From the results obtained, the asymmetry between the discourse of the participants and their course of action in the classroom was very noticeable: the participants considered indiscipline vocal behaviour (such as talking and shouting), play involving movement, as well as aggressive and destructive behaviour. Despite that, when taking into account the data collected during classroom observation which showed high incidence of talking and some physical movement, the teachers did not act as if they considered such events indiscipline; besides that, in the rare events of light (verbal and physical) aggression to class peers, the teachers action showed they saw such events as indiscipline, an attitude coherent with what they had declared. It is also noticeable that teachers exclude themselves when providing explanations about the causes of indiscipline: participants provide psychologically and sociologically-based explanations, leaving aside aspects related to their performance; moreover, similar information appeared in the suggestions on how to prevent indiscipline, which in turn focus on aspects that do not depend on teacher action. Yet, although the solution to indiscipline may be in aspects external to the classroom environment, when indiscipline occurs in the classroom, the teachers act so as to eliminate it, which shows that they attribute such role to themselves and not to the school principal or the students parents. Regarding the educational project, a comparison was made between the performance of participants in Pre-Tests and Post-Tests so as to evaluate the effects produced. The results of Pre-Tests and Post-Tests show specific changes in the way functional analysis was used by participants; however, results provided insufficient evidence that participants had adopted a functional analysis of indiscipline in the classroom. The participants acceptance of the project and the institutional conditions were also analysed. As for the acceptance of the proposal, the positive aspects included the use of descriptive episodes of real life situations, and the group dynamics used. Written activities and some strategies used by the researcher were considered negative. In the final discussion presented in this thesis, in addition to dealing with aspects related to the teachers points of view concerning indiscipline in the classroom, there was a reflection about the possibility of developing an educational project for the conditions offered by the educational area